Impact of Earnings Variability and Regulatory Measures on Income Smoothening in Islamic Banks: Evidence from an Emerging Market - Malik, Amina; Zaheer Butt, Babar; Din, Shahab Ud; Aziz, Haroon (Public Finance Quarterly, 2020)
This study focuses on identification of income smoothening practices and the impact of stringent regulations on income smoothening of Islamic banks listed on Pakistan Stock Exchange (PSX) for the period of 2010 to 2018. The frequency of income smoothing activities is evaluated through loan loss provisions (LLPs). Data has been retrieved through bank financial statements and financial statements analysis (FSA) issued by State Bank of Pakistan (SBP). In order to test income smoothening in Islamic banks, regression model has been employed. The findings of the study reveal that Islamic banks operating in Pakistan use income smoothening practices to achieve their objectives despite presence of Shariah Law. Further, the study also reveals that imposition of capital adequacy ratio through Basel Accords has significant and positive impact on reduction of income smoothing activities. Moreover, increase in the size of bank in terms of asset size has also positive impact through reduction of income smoothening in Islamic banks of Pakistan. Moreover, non-performing loans (NPL) and total loans (TL) also increase income smoothening. Similarly, GDP also increases income smoothening. The study provides sight not only for auditors and regulators but also for investors and general public. The study also highlights that there is a dire need for regulators to adopt strict and close monitoring on the distribution of earnings to avoid smoothening practices. Results also offer inputs to policymakers to customize their policies so that smoothening practices may be curtailed in Islamic banks and true picture be provided to investors about bank performance.